(untitled) (Homoeopathy for All, 2025)
Background: Atopic disorders are a significant global health issue, affecting 5%–30% of the population. Type I hypersensitivity reactions, mediated byz immunoglobulin E (IgE), play a central role in atopic respiratory complaints. This study evaluates the effect of Azadirachta indica 30C in reducing serum IgE levels. ¹⁻³ Objective: To assess the variation of serum IgE levels before, during, and after intervention with Azadirachta indica 30C in patients with atopic respiratory complaints. Materials and Methods: Thirty cases of atopic respiratory complaints (diagnosed based on clinical history, CMDT guidelines, and initial serum IgE levels) were selected using purposive sampling. Azadirachta indica 30C was administered twice daily for 2 weeks, with placebos given in between, and patients were followed for 3 months. Serum IgE levels were measured monthly. Data were analyzed using mean, standard deviation, and repeated measures ANOVA. Results: ANOVA showed a highly significant reduction in serum IgE levels (P = 0.000). Pairwise comparisons demonstrated significant decreases between pre and during-treatment (P = 0.007) and during- and post-treatment (P = 0.016) measurements. Conclusion: Homoeopathic treatment with Azadirachta indica 30C leads to a significant reduction in serum IgE levels in patients with atopic respiratory complaints.